Physical performance trajectories and mortality among nursing home residents: results of the SENIOR cohort. (17th March 2020) - Charles, Alexia; Detilleux, Johann; Buckinx, Fanny; Reginster, Jean-Yves; Gruslin, Bastien; Bruyère, Olivier
Abstract: Background: Previous studies have shown that older people can experience a considerable change in their physical performance (PP) over time. Objectives: To identify PP trajectories and their association with mortality among nursing home residents who were followed up for 3 years. Design: Three-year longitudinal observational study. Setting: Subjects of the SENIOR cohort. Subjects: Six hundred and four nursing home residents with a mean age of 82.9 ± 9.1 years. Methods: Baseline characteristics and the date of death were collected from the medical records. PP was assessed annually by the short physical performance battery (SPPB) test. Multiple imputations were performed to manage the missing data. PP trajectory groups were estimated using latent growth curve analysis. Cox proportional hazard regression models were applied to examine the risk of mortality according to the PP trajectory groups. Results: Three PP trajectory groups were identified: slow decline ( N  = 96), moderate decline ( N  = 234) and fast decline ( N  = 274). After adjustments for potential confounding variables and the baseline SPPB scores, the residents in the fast decline and moderate decline trajectory groups had an increased risk of mortality compared to those in the slow decline trajectory group, with hazard ratio values of 1.78 (95% confidence interval [CI] = 1.34–2.26) and 1.37 (95% CI = 1.10–1.66), respectively. Conclusions: PP trajectories provide value-added information to baseline geriatric assessments and could be used for predicting 3-year mortality among nursing home residents. It may be important to regularly monitor the SPPB score and signal an alert when a fast decline in PP is detected in older people.